2018
DOI: 10.3389/fpsyg.2018.01874
|View full text |Cite
|
Sign up to set email alerts
|

Work Engagement and Flourishing at Work Among Nuns: The Moderating Role of Human Values

Abstract: Faith-based organizations are a key player in major sectors of activity for maintaining the welfare state, including health, education, and social services. This paper uses a multivariate regression model in an attempt to identify the factors that affect the relationship between work engagement and flourishing. The paper also discusses the empirical research gap that has been identified in the literature about the moderated effect of human values on this relationship. This study is based on a sample of 142 nun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 55 publications
1
26
0
1
Order By: Relevance
“…Second, the results affirming that conservationist workers may be engaged in faith-based institutions are also in line with investigations explaining that these groups are characterized by values such as tradition, obedience, social order and humility (Ariza-Montes et al, 2018a). In these entities, there is a positive direct relationship between spiritual resources and work engagement (Bickerton et al, 2014).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Second, the results affirming that conservationist workers may be engaged in faith-based institutions are also in line with investigations explaining that these groups are characterized by values such as tradition, obedience, social order and humility (Ariza-Montes et al, 2018a). In these entities, there is a positive direct relationship between spiritual resources and work engagement (Bickerton et al, 2014).…”
Section: Discussionsupporting
confidence: 84%
“…In addition, as explained before, there is a positive direct relationship between work engagement and spiritual resources, as the link with God generates more work engagement in religious workers than in other groups of people (Bickerton et al, 2014). Among these religious and social employees (both with a pronounced social perspective), collectivism (self-transcendence) prevails over individualism (self-enhancement) (Kim, 2012;Ariza-Montes et al, 2018a). Therefore, self-transcendence (benevolence and universalism) should lead workers of faith-based organizations to be more engaged in their work.…”
Section: Direct Relationship Between Human Values and Work Engagementmentioning
confidence: 89%
“…The existing evidence suggests that the basic assumption of the JD-R theory could be applied to assess employees' well-being in a broad variety of organizations (e.g., Schaufeli and Taris, 2014;Lesener et al, 2019). However, it has been noted that specific investigations of employees' well-being within religious organizations are rather limited (Bickerton et al, 2014: Miner et al, 2015Roof, 2015;Ariza-Montes et al, 2017;Ariza-Montes et al, 2018). Furthermore, previous research on employee health and well-being within religious organizations has predominately focused on stress and ill health.…”
Section: Occupational Well-being Within Religious Organizationsmentioning
confidence: 99%
“…Research into the relationship between commitment to work and the sense of self-realization described as "flourishing" shows that this "flourishing" is mediated by the subject's relation to values, especially to humanistic values. Research involving 144 Catholic nuns has shown a direct dependence between their commitment to helping the needy and their personal development in their professional environment (Ariza-Montes, Molina-Sanchez, Ramirez-Sobrino, & Giorgi, 2018). Personal development in a professional context is enhanced by the correspondence between the characteristics of the workplace and personal competences.…”
Section: Charity and Social Services Offered By Faith-based Organimentioning
confidence: 99%